2013
DOI: 10.1093/humrep/des455
|View full text |Cite
|
Sign up to set email alerts
|

Vitrification preserves proliferation capacity in human spermatogonia

Abstract: The present study was supported by a grant from the Fonds National de la Recherche Scientifique de Belgique (grant Télévie N° 7. 4.572.09.F). The authors declare that there is no conflict of interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
107
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 39 publications
6
107
0
Order By: Relevance
“…However, vitrification represents an innovative alternative strategy for pre-pubertal testicular tissue cryopreservation. Indeed, it has been suggested that vitrification may be an effective method to cryopreserve testicular tissue and maintain its ability to initiate (Poels et al, 2013) or even complete (Abrishami et al, 2010;Kaneko et al, 2013;Yokonishi et al, 2014) spermatogenesis after thawing. Vitrification is a physical phenomenon that allows, by an ultrafast cooling velocity, the transformation of a liquid into an amorphous glassy solid (Fahy et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, vitrification represents an innovative alternative strategy for pre-pubertal testicular tissue cryopreservation. Indeed, it has been suggested that vitrification may be an effective method to cryopreserve testicular tissue and maintain its ability to initiate (Poels et al, 2013) or even complete (Abrishami et al, 2010;Kaneko et al, 2013;Yokonishi et al, 2014) spermatogenesis after thawing. Vitrification is a physical phenomenon that allows, by an ultrafast cooling velocity, the transformation of a liquid into an amorphous glassy solid (Fahy et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In mice, some promising recent results have shown good preservation of vitrified/warmed pre-pubertal testicular tissue after allografting (Baert et al, 2012) or short term in vitro organ culture (Curaba et al, 2011b;Gouk et al, 2011). However, CSF and vitrification protocols resulted in similar SSCs survival rates, suggesting that multifactorial parameters other than the cryopreservation procedure may be implicated (Poels et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, cryopreservation of cellular aggregates or tissues may allow for the isolation and culture of SSCs from frozen-thawed tissues in order to mimic conditions that will occur in oncology patients. 35,36 To date, immature testicular pieces have been cryopreserved by slow-freezing and vitrification in both mice 37 and humans 38,39 and have been hetero-grafted beneath the tunica albuginea of a busulfantreated recipient testis. These studies demonstrate that spermatogonia can survive in xenogeneic recipients after cryopreservation and therefore result in an offspring after sperm microinsemination.…”
Section: Introductionmentioning
confidence: 99%
“…Other authors have analyzed the histology and morphology of testicular tubules stained with hematoxylin-eosin (Baert et al, 2012;Poels et al, 2013). The main limitation of this method is that it cannot definitively evaluate the impact of the procedure on the function of cryopreserved testicular tissue (Kvist et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Several animal (Curaba et al, 2011;Gouk et al, 2011;Baert et al, 2012;Poels et al, 2012;Liu et al, 2013) and human (Curaba et al, 2011;Baert et al, 2013;Poels et al, 2013;Sá et al, 2012) vitrification in the cryopreservation of prepubertal testicular tissue with encouraging results. These studies have shown that the preservation of testicular cells and tissue through vitrification has been at least as effective as traditional slow freezing protocols (Curaba et al, 2011;Baert et al, 2012;Sá et al, 2012).…”
Section: Introductionmentioning
confidence: 99%